Diel activity and short‐distance movement pattern of the European spiny lobster, Palinurus elephas, acoustically tracked. (11th February 2014) - Giacalone, Vincenzo M.; Barausse, Alberto; Gristina, Michele; Pipitone, Carlo; Visconti, Valerio; Badalamenti, Fabio; D'Anna, Giovanni
Abstract This paper presents the results of the application of an ultrasonic telemetry system to the investigation of short‐term movements in the European spiny lobster, Palinurus elephas, in a coastal area of NW Sicily (Central Mediterranean Sea). Ten lobsters were tagged with miniaturized transmitters and released over a favourable habitat and their movements then recorded by means of nine automated receivers with the objective of investigating post‐release displacement, home‐range extension, movement patterns, activity rhythm and the influence of lunar light intensity on lobster activity. Acoustic detection data were used to assess activity and home range using estimates of horizontal and vertical movements and minimum convex polygons, respectively. Continuous wavelet transform (CWT) analysis was applied to time series of position data. Acoustic data from five of 10 lobsters were successfully recorded across a 78‐day study period between April and June 2008. All of them displayed an activity pattern characterized by diurnal sheltering and nocturnal foraging, with higher activity (i.e., longer distances travelled) at night. Their home range measured between 1629 and 8641 m2, and all lobsters relocated every 4.6 days on average, probably in search of unexploited feeding grounds. For this reason we hypothesize a nomadic movement pattern for our tagged lobsters. CWT analyses highlighted a 24‐h periodicity in lobster activity, with higher activity from sunset to sunrise. No clear influence of moon phase on lobster activity was detected.